Engineering Multi-Agent Systems First International Workshop, EMAS 2013, St. Paul, MN, USA, May 6-7, 2013, Revised Selected Papers - Cossentino, Massimo; El Fallah Seghrouchni, Amal.; Winikoff, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the First International Workshop on Engineering Multi-Agent Systems, EMAS 2013, held in St. Paul, MN,  USA, in May 2013. The 19 full papers  were carefully reviewed and selected from 30 submissions. The focus of the papers is on following topics: agent-oriented software engineering, declarative agent languages and technologies, and programming multi-agent systems.
SeSaMe: Towards a Semantic Self Adaptive Middleware for Smart Spaces -- Propagating AUML Protocols to Detailed Design -- 2COMM: A Commitment-Based MAS Architecture -- Benchmarking Communication in Actor- and Agent-Based Languages -- Applying an O-MaSE Compliant Process to Develop a Holonic Multiagent System for the Evaluation of Intelligent Power Distribution Systems -- Embedding Agents in Business Processes Using Enterprise Integration Patterns -- Belief Caching in 2APL -- Deciding between Conflicting Influences -- A Multi-agent Approach to Professional Software Engineering -- Alternatives to Threshold-Based Desire Selection in Bayesian BDI Agents -- Engineering Pervasive Multiagent Systems in SAPERE -- An Infrastructure for the Design and Development of Open Interaction Systems -- GoalSPEC: A Goal Specification Language Supporting Adaptivity and Evolution -- Mutation Operators for the GOAL Agent Language -- Automatic BDI Plan Recognition from Process Execution Logs and Effect Logs -- Multi-Agent Programming Contest 2013 -- SMADAS: A Team for MAPC Considering the Organization and the Environment as First-Class Abstractions -- Engineering a Multi-Agent System in GOAL -- Improving the LTI-USP Team: A New JaCaMo Based MAS for the MAPC 2013 -- Multi-Agent Programming Contest 2013: TUB Team Description -- Prior State Reasoning in Multi-agent Systems and Graph-Theoretical Algorithms -- Multi-agent Programming Contest 2013: The Teams and the Design of their Systems.
Keywords: Artificial intelligence; Software engineering; Computer programming; Computer science; Artificial Intelligence; Software Engineering; Programming Techniques; Computer Science, general